The first confirmed cleptine cuckoo wasp from Baltic amber with description of a new subgenus (Hymenoptera: Chrysididae) - Lucena, Daercio A. A. [UNESP]; Melo, Gabriel A. R. (Taylor & Francis, 2025)
Cleptes (†Electrocleptes) trematossubgen. et sp. nov. is described based on a remarkable fossil from Baltic amber. This new subgenus resembles some extant Cleptes from the Holarctic region but can be differentiated by a combination of unique characteristics, including distinctly elongated ventral sensilla on F2–F4, anterior pronotal flange wide and transversely cross-ridged, mesopleuron coarsely punctate, and profemur distinctly enlarged mesodistally. Additionally, †Uromesitius caudatus Brues, 1933 is herein interpreted as belonging to the crown group of Cleptinae. We discuss previous records of extinct taxa disputedly assigned to Cleptinae and highlight the morphological characters which help to identify this taxon. The new fossil fills a significant temporal gap, thus enhancing our understanding on the taxonomy and evolutionary history of Cleptinae. urn:lsid:zoobank.org:pub:0C4D4F68-F590-40BD-99AF-ED8E07AA7907.
Keywords: Aculeata; Chrysidoidea; morphology; Paleogene; systematics